MEMBANGUN RESILIENSI KOLEKTIF MASYARAKAT TRADISIONAL MELALUI PENDIDIKAN MULTIKULTURAL - Ign Y Kristio Budiasmoro (Graduate School, Universitas Negeri Yogyakarta, 2014)
Traditional peoples order with religiosity and spirituality in harmony with nature, often become vulnerable when the quality and carrying capacity decreases due to the economic exploitation. Diversity of perspectives on the diversity of socio-cultural reality there are many causes for miscommunication and the seeds of social conflict. Conditions of such a society will be increasingly vulnerable in the next collective powerlessness and they will easily become the object of the struggle for economic exploitation. Multicultural education plays an important role in the community to raise awareness of the importance of seeking equality of access rights to live more dignifiedly. Strengthening and revealing of traditional culture values would enhance the collective resilience. The implementation of multicultural education and ethnic identity are expected to become increasingly affirmed. Thus multicultural education is able to contribute to society’s in awareness of equality and rights to live more dignifiedly.Keywords: collective resilience, multicultural education, ethnic identity